Biomarkers in the Diagnosis of Rare Diseases. Innovative approaches by predictive and personalized medicine - Gakharia, Tatia; Besiashvili, Nino; Sulashvili, Nodar (Caucasus Journal of Health Sciences and Public Health, 2019)
Biomarkers are key tools and can provide crucial information on the complex cascade of events and molecular mechanisms underlying pathophysiology and the secondary pathologic cascades of rare diseases. Obtaining a profile of distinct classes of biomarkers reflecting core pathologic mechanisms could enable us to identify and characterize the initial injury. Thus, they represent a logical adjunct to improve diagnosis. Regular monitoring both for disease onset and progression but also demonstrating the benefit of potential treatment are of high value for the patients. Biomarkers bring rationality in the treatment of patients with rare diseases. We present review of the biomarkers, their role in rare diseases diagnostic process and implementation in currently available predictive and personalize medicine, while characterizing their potential role and applications in diagnosis, monitoring, drug discovery. In reviewing these concepts, we discuss epidemiological and interventional clinical studies as the important and powerful tool in biomarkers development. Based on several examples outline the advantages and limitations, perspectives and drawbacks, for their use at the clinic.